Cellulitis with Leukocytopenia as an Initial Sign of Acute Promyelocytic Leukemia - Sachiko Sakamoto; Naoki Oiso; Masakatsu Emoto; Shusuke Uchida; Ayaka Hirao; Yoichi Tatsumi; Itaru Matsumura; Akira Kawada (Karger Publishers, 2012)
Patients with hematologic malignancies are immunosuppressive and may develop cutaneous or invasive infections as a primary sign of immune suppression. Acute promyelocytic leukemia (acute myeloid leukemia M3) is caused by translocation of reciprocal chromosomal rearrangement t(15;17), which produces an oncogenic protein. We herein describe a 71-year-old man having cellulitis with leukocytopenia as a first sign of acute promyelocytic leukemia. Dermatologists and hematologists should keep in mind that patients with a hematologic malignancy, such as acute promyelocytic leukemia, can develop cellulitis with leukocytopenia.